1997
DOI: 10.1177/0887302x9701500204
|View full text |Cite
|
Sign up to set email alerts
|

The Textile Waste Lifecycle

Abstract: With growing attention to environmental responsibility towards solid waste management, the textile and apparel industry has expanded its efforts to reduce disposal of post-producer textile waste in landfills. At the same time, finding alternative methods for the disposal of post-consumer textile waste is assuming greater importance. This exploratory research presents a model of the textile waste lifecycle. The model is intended to better explain events associated with the production and disposal of post-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 1 publication
0
42
0
Order By: Relevance
“…Garments made from synthetic fibers can also be recycled chemically, where the fiber is broken down to the molecular level and then repolymerized. Several LCA studies have been conducted comparing reuse/ recycling of textile waste with virgin materials [32,33]. This research quantified the energy burden associated with the processing and transportation of collected (donated) domestic clothing for potential reuse or reprocessing, and showed that all processes, including the energy burden associated with retailing and distribution of the donations, have been insignificant compared with the energy consumed during the manufacture of these items from virgin materials.…”
Section: Reusable Recycled Materials and Waste Reductionmentioning
confidence: 99%
“…Garments made from synthetic fibers can also be recycled chemically, where the fiber is broken down to the molecular level and then repolymerized. Several LCA studies have been conducted comparing reuse/ recycling of textile waste with virgin materials [32,33]. This research quantified the energy burden associated with the processing and transportation of collected (donated) domestic clothing for potential reuse or reprocessing, and showed that all processes, including the energy burden associated with retailing and distribution of the donations, have been insignificant compared with the energy consumed during the manufacture of these items from virgin materials.…”
Section: Reusable Recycled Materials and Waste Reductionmentioning
confidence: 99%
“…The present invention provides nonwoven fabric prepared with recycled cotton and recycled polyester blended fibers with such a unique texture and properties which makes it suitable for preparing the various household and commercial products out of it [6][7][8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…These fibres could not be used directly in the apparel industry but have a high potential in the manufacturing of recycled woven and nonwovens fabrics that are quite promising materials in the current market. Use of recovered synthetic fibrous waste is particularly attractive as the processing characteristics of properly recovered synthetic do not differ much from those of original synthetic staple and cut filaments [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequent of their inherent high pollution potential, textile industries contribute significantly to the international debates relating to international trans-boundary river systems [5,6]. Efforts are being made to reduce the extent of pollution such as landfilling the sludge that comes from the textile industries, which could also present a future challenge if the landfills are not properly constructed [7]. However, associated with the sludge is a release of copious amount of dyed wastewater that is used for dying the fabrics which is a nightmare to the sewerage authorities in places that host this industry [8].…”
Section: Introductionmentioning
confidence: 99%